Touchscreen-Based Cognitive Tasks Reveal Age-Related Impairment in a Primate Aging Model, the Grey Mouse Lemur (Microcebus murinus) - Joly, Marine (Public Library of Science, 2014)
Mouse lemurs are suggested to represent promising novel non-human primate models for aging research. However, standardized and cross-taxa cognitive testing methods are still lacking. Touchscreen-based testing procedures have proven high stimulus control and reliability in humans and rodents. The aim of this study was to adapt these procedures to mouse lemurs, thereby exploring the effect of age. We measured appetitive learning and cognitive flexibility of two age groups by applying pairwise visual discrimination (PD) and reversal learning (PDR) tasks. On average, mouse lemurs needed 24 days of training before starting with the PD task. Individual performances in PD and PDR tasks correlate significantly, suggesting that individual learning performance is unrelated to the respective task. Compared to the young, aged mouse lemurs showed impairments in both PD and PDR tasks. They needed significantly more trials to reach the task criteria. A much higher inter-individual variation in old than in young adults was revealed. Furthermore, in the PDR task, we found a significantly higher perseverance in aged compared to young adults, indicating an age-related deficit in cognitive flexibility. This study presents the first touchscreen-based data on the cognitive skills and age-related dysfunction in mouse lemurs and provides a unique basis to study mechanisms of inter-individual variation. It furthermore opens exciting perspectives for comparative approaches in aging, personality, and evolutionary research.